Econometrics case study: Analysis of factors influencing the poverty rate in the Special Region of Yogyakarta Province - Wibowo, Bintang Cahyo; Akbar, Fadhil Ichwan Al; Pranadita, Natasya Erischa; Sampurnani, Salsabila; Antriyandarti, Ernoiz (Social, Ecology, Economy for Sustainable Development Goals Journal, 2024)
Background: This research is an econometrics case study aimed at addressing two research questions. Firstly, to provide an overview of the Special Region of Yogyakarta Province. Secondly, to identify the factors influencing the poverty rate in the province. The study utilizes the concepts of poverty, provincial minimum wage, Human Development Index (HDI), economic growth, and unemployment rate. Method: Methodologically, the province is chosen as the research location due to its poverty rate that requires attention and its distinctive social, economic, and geographical characteristics. The data used are secondary data, analyzed using multiple linear regression and normality tests. Findings: The findings of this study are as follows. Firstly, the Special Region of Yogyakarta Province is situated between 7°33' LS - 8°12' LS and 110°00' BT - 110°50' BT, with a land area of 3,185.8 km2. The province comprises 4 regencies and 1 municipality. Secondly, the factors influencing the poverty rate in the Special Region of Yogyakarta Province are the Human Development Index (HDI) and the unemployment rate. Conclusion: The conclusion is that the poverty rate in the Special Region of Yogyakarta Province is influenced by the Human Development Index (HDI) and the unemployment rate. The recommendations that can be given are to increase the HDI and reduce the unemployment rate through various government initiatives such as improving education, creating jobs, and encouraging economic activities. Novelty/Originality of this article: This study identifies factors that influence poverty levels using multiple linear regression. The results show that the Human Development Index (HDI) and poverty rates significantly influence poverty rates in this province.